EFFECTIVE AND INTERACTIVE STRATEGIES TO ENHANCE READING AND COMPREHENSION SKILLS IN EFL CLASSROOMS - Abdubaitova Ruzigul (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Reading comprehension is an essential academic skill and a key indicator of literacy development, particularly for learners of English as a Foreign Language (EFL). Traditional reading methods often fall short in engaging students and fostering deep understanding.  This  paper  explores  effective  and  interactive  strategies  aimed  at improving reading comprehension, focusing on student-centered approaches such as reciprocal teaching, interactive read-alouds, literature circles, and the integration of technology.  These  methods  support  vocabulary  development,  critical  thinking,  and metacognitive  awareness,  ultimately  creating  more  inclusive  and  effective  reading environments.